Effects of Marketing Strategies on the Performance of Tourism and Hospitality Enterprises in Uganda: Case Study of Bwindi Impenetrable National Park. - Asiimwe, Dennis (Kabale University., 2024)
The study was about the effects of marketing strategies on the performance of tourism and hospitality enterprises: A case study of Bwindi Impenetrable National Park in Uganda. The objectives of the study were to assess the different marketing strategies in tourism and hospitality enterprises in Bwindi Impenetrable National Park, to identify the role of marketing in tourism and hospitability enterprises in Bwindi Impenetrable National Park, and to find out challenges facing marketing in tourism and hospitability in Bwindi Impenetrable National Park. The research used a descriptive study design depending on the characteristics of the study. A sample of 76 respondents was used, and data was collected using a questionnaire directed to technical leaders, politicians, opinion leaders, and other stakeholders (local government staff, tourists, central government) in the area. Data was analyzed using frequencies where percentages were derived for easy interpretation. Findings show that they create engaging and informative content related to travel destinations, local attractions, and hospitality services. Some respondents also showed that leverage popular social media platforms such as Instagram, Facebook, Twitter, and Pinterest. Some respondents agreed that collaborating with influencers and travel bloggers to reach a broader audience. From the findings, tourism and hospitality businesses rely on marketing to create and enhance brand awareness. Effective marketing campaigns contribute to building a positive brand image, which is crucial for attracting new customers and retaining loyal ones. According to the results, sustainability practices were mentioned by the respondents in that encouraging sustainable tourism practices and responsible visitor behavior is crucial. This involves minimizing the ecological footprint of tourists and ensuring that the influx of visitors does not harm the natural environment. The study concludes that over the last two decades, the Ugandan Tourism industry has grown very rapidly as compared to other industries in the service sector and it has the potential to generate employment earn large amounts of foreign exchange, and increase the country’s overall economic and social development. But it’s not a peak point or performance, much more remains to be done. The study recommends there is a need to conduct thorough market research to understand the preferences, behaviors, and needs of the tourists. Tailor the marketing strategies to address the specific interests and demographics of potential customers. There is a need to clearly communicate the unique features and experiences that set the tourism destination, hotel, or service apart from competitors.